Mother’s Parenting Stress and Marital Satisfaction During the Parenting Period: Examining the Role of Depression, Solitude, and Time Alone - Dong, Simeng; Dong, Qinnan; Chen, Haiyan; Yang, Shuai (Frontiers in Psychology, 2022)
This study examines the mechanism of maternal parenting stress on marital satisfaction based on the Vulnerability-Stress-Adaptation Model (VSAM), and draws on the needs theory of Buchholz (1997) to explore the role of alone time in marital relationships under different solitude preferences. The marital satisfaction Scale, Self-rating Depression Scale (SDS), Parenting Stress Scale (PSS), Preference for Solitude Scale (PSS), and alone time scale were used to conduct a questionnaire survey of 1387 Chinese mothers in their parenting stage. The results found that: (1) In the overall group and the high and low solitude preference level group, depression plays a significant mediating role between parenting stress and marital satisfaction. (2) For mothers who prefer solitude, alone time can reduce the positive impact of parenting stress on depression, and but it cannot alleviate the negative impact of parenting stress and depression on marital satisfaction. (3) In the low solitude preference level group, alone time can aggravate the positive impact of parenting stress on depression and the negative impact of parenting stress on marital satisfaction.